Floristic composition at biodiversity protection area in Lubuk Kakap, District of Ketapang, West Kalimantan - SUGENG BUDIHARTA (Biodiversitas Journal of Biological Diversity, 2010)
Budiharta S (2010) Floristic composition at biodiversity protection area in Lubuk Kakap, District of Ketapang, West Kalimantan. Biodiversitas 11: 151-156. A study on floristic composition has been conducted at biodiversity protection area (Kawasan Perlindungan Plasma Nutfah, KPPN) of PT. Suka Jaya Makmur in Lubuk Kakap, District of Ketapang, West Kalimantan. Two sampling methods were used: Point-Quarter sampling (Quadrant method) of 50 m was applied to class of tree, and 2x2 m2 plot sampling to class of sapling. Of 20 sampling units, 48 species of tree (belong to 27 genera and 13 families) and 94 species of sapling (belong to 54 genera and 28 families) were recorded. Shannon-Wiener diversity index (H’) were 3.54 and 3.49 for tree and sapling respectively, while Pielou evenness index (J’) were 0.91 and 0.77 for tree and sapling respectively. Forest ecosystem in this area can be classified as lowland ever wet tropical rain forest which dominated by dipterocarps species. Species of sapling with the highest importance value index were Shorea laevis, Hopea dryobalanoides and Shorea sandakanensis, while that of tree included Dipterocarpus caudiferus, Shorea laevis and Dryobalanops sp. The floristic composition at family level showed comparatively similar pattern with that at other sites inKalimantan although composition at species level was different.Key words: biodiversity protection area, dipterocarpaceae, floristic composition, High Conservation Value Forest (HCVF), production landscape